Biosynthesis and Characterization of Silver Nanoparticles Using Cleistanthus collinus; Investigation on Molecular Mechanism of Apoptosis Cell Death Against Lung Cancer Cells - Kanipandian, Nagarajan; Ramesh, Ramar (Asian Pacific Journal of Cancer Biology, 2024)
Background: The discovery of novel molecular and cellular signaling pathways for cancer medicines would enhance the efficacy of cancer therapy. In the current study, we made an effort to explore the mitochondrial-mediated apoptosis cell death signaling pathway in A549 lung cancer cells by silver nanoparticles (AgNPs) synthesized from leaf extract of Cleistanthus collinus. Methods: In-depth, A549 lung cancer cells were treated with AgNPs, and further studies such as HOECHST 33342, AO/EB, Rhodamine-123 staining, flowcytometry, RT-PCR, and Western blotting techniques (24, 48, and 72 h) evidenced apoptosis pathway in cancer cells. Results: Indeed, the microscopic studies proved that AgNPs-treated lung cancer cells appeared with cell shrinkage, membrane swelling, and apoptotic body formation whereas the untreated cells (control) failed to show any morphological consequences. The flow cytometry analysis revealed the G2/M phase of cell cycle arrest by cells were accumulated in large numbers. The RT-PCR data confirmed the expression (Bax and p53) and suppression (Bcl 2) apoptosis-responsive genes in cancer cells. Finally, immunoblotting proved the increased expression of cytochrome c, initiator caspase 9, and executioner caspase 3, which are effective proteins of intrinsic apoptosis activation. Conclusion: Ultimately, the overall present investigations confirmed the mitochondrial signaling pathway played a key role in inducing apoptosis in A549 cancer cell death and demonstrated that AgNPs are novel therapeutic agents for cancer nanomedicine